Tuweb (Web-Based Tutorial) with Scrapbooks and Videos to Improve Students' Learning Outcomes (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2023)
Online learning has its perks and challenges to student learning outcomes. This study aims to develop educational products that meet the validity, effectiveness, and practicality criteria in the form of scrapbooks and videos on Tu web (Web-based Tutorial) for the Statistics Education course to tackle these negative impacts. In this developmental research, field tests were conducted on 83 Open University students from three different study groups in East Java. The development stages started from planning, exploratory studies, initial product development, expert validation, and initial field tests had been carried out in the previous year. The instruments used in this research are Tutorial Activity Design, Tutorial Activity Unit, scrapbook, video, student response questionnaire, and final test. The results showed that students responded positively to the use of these products in the Tuweb of Statistics Education courses. Since all students solved problems in the scrapbook, the product met the practicality criteria. Furthermore, the average student learning outcomes were 82.17 with a minimum of 70, better than students who did not participate in the study. Therefore, these products met the effectiveness criteria. As the research has demonstrated, the scrapbooks and videos developed can improve student learning outcomes in the Statistics Education course.